The Effect Of Sales Promotion On Consumer Purchase Decisions Pt Ria Indah Mandiri Sumedang - Ginanjar, Yayat; Arafah, Negri Nurkhotif (Universitas Sebelas April, Fakultas Ekonomi dan Bisnis, 2024)
The company has a goal that is to earn profits, one of the activities that can generate profits is sales. With the achievement of sales effectiveness, the company can achieve its goals. One of the efforts made by the company to achieve sales effectiveness is by way of promotion. This study aims to determine the effect of sales promotions on consumer purchasing decisions at PT Ria Indah Mandiri Sumedang. This study uses a descriptive research method approach with quantitative analysis techniques, carried out through survey methods. Data collection techniques were carried out by means of observation and questionnaires. Taking the number of respondents using the Slovin Formula, namely as many as 100 respondents. The data analysis technique uses Statistical Package For Social Science (SPSS) 21. The analytical method used in this study is a simple linear regression method, t test, correlation test, coefficient of determination. SPSS V.21 calculation results get a simple linear regression equation Y = 14.050 + 0.762. The above analysis is acceptable because the sales promotion variable has a positive and significant effect on consumer purchasing decisions at PT. Ria Indah Mandiri Sumedang with a regression coefficient of 0.762